Bioaccumulation, trophodynamics and ecotoxicity of antimony in environmental freshwater food webs. Issue 22 (17th November 2017) - Obiakor, Maximilian Obinna; Tighe, Matthew; Pereg, Lily; Wilson, Susan C.
ABSTRACT: This article reviews relevant literature on antimony (Sb) bioaccumulation, trophodynamics and ecotoxicity in freshwater environments, and identifies current information gaps. Both autotrophs and heterotrophs can bioaccumulate Sb, and elevated concentrations in tissues are mostly associated with anthropogenic sources. The degree of bioaccumulation is governed by species and trophic ecology. Field studies indicate that Sb does not biomagnify in food webs consisting of autotrophs, macroinvertebrate consumers, tadpoles, and fish. A range of studies demonstrate that Sb is toxic to aquatic organisms but whether differential effects occur in different organisms is unclear. Toxicity depends on the compounds supplying the Sb, and studies do not always show that Sb(III) is more toxic than Sb(V). Genotoxicity in aquatic organisms with Sb exposure is not quantified, and evidence for genotoxic effects in bacteria is contradictory with toxicity mechanisms little understood. This review identifies several knowledge gaps that limit informed Sb hazard assessment in aquatic systems and hinder establishing reliable protective guidelines. In particular, limited data is available for Sb bioaccumulation in different geographic regions across spatiotemporal scales, on laboratory and field studies examining different trophic links and biotransference, and Sb interactions with cellular targets in acute and chronic toxicity.